Application of geostatistical analyst methods in discovering concealed gold and pathfinder elements as geochemical anomalies related to ore mineralisation - Lindagato, Philemon; Li, Yongjun; Yang, Gaoxue; Duan, Fenghao; Wang, Zuopeng (Geologos, 2018)
The study area in the West Junggar Basin is known to be rich in hydrothermal gold deposits and occurrences, even though there has been minimum exploration in the area. It is here hypothesised that this area could host more gold deposits if mineral exploration methods were to be reinforced. This research is aimed at identifying geochemical anomalies of Au, and determining possible factors and conditions which facilitate the formation of anomalies by referring to As and Hg as gold pathfinders. Geostatistical analyst techniques have been applied to 9,852 stream sediments and bedrock data collected on a total surface of 1,280 km2 of West Junggar, Xinjiang (northwest China). The kriging interpolation and quantile-quantile plot methods, combined with statistical methods, successfully identified both Au and its pathfinders’ anomalies. In the present study, median was considered as background values (10.2 ppm for As, 9.13 ppb for Hg and 2.5 ppb for Au), whereas the 95th percentile were threshold values (28.03 ppm for As, 16.71 ppb for Hg and 8.2 ppb for Au) and values greater than thresholds are geochemical anomalies. Moreover, the high concentrations of these three discovered elements are caused primarily by hydrothermal ore mineralisation and are found to be controlled mainly by the Hatu and Sartohay faults of a northeast-southwesterly direction as well as their related secondary faults of variable orientation, which facilitate the easy flow of hydrothermal fluids towards the surface resulting in the formation of geochemical anomalies. Most of anomalies concentration of Au are found near the mining sites, which indicates that the formation of new Au anomalies is influenced by current or previous mining sites through geological or weathering processes. In addition, the low concentration of gold and its pathfinders found far from active gold mine or faults indicates that those anomalies are formed due to primary dispersion of hosting rock.